Mapping and monitoring soil erosion in a watershed in western Algeria - Bouderbala, Djazia; Souidi, Zahira; Donze, Frédéric; Chikhaoui, Mohamed; Nehal, Laounia (Arabian journal of geosciences, 2018)
Fergoug watershed is subject to severe water erosion and land degradation that threaten agricultural sustainability for local populations. Soil loss and degradation by water erosion were estimated using the universal soil loss equation (USLE). The spatial distribution of soil losses was determined using the following parameters: the erosivity factor (R), obtained using climatic data from 12 local stations over a period of 41 years; the land cover factor (C), obtained using LandSat-TM satellite imagery 7 and 8; the erodibility factor (K), estimated from soil particle size analyses; and the topographic factor (LS), obtained from a digital terrain model. The Fergoug watershed is characterized by complex topography, and the topographic factor reached a value of 14.29. The erodibility factor K ranged from 0.08 to 0.38, and high values were recorded for about 20% of the watershed. The rainfall erosivity factor R ranged between 212.32 and 146.73 from east to west. The plant cover factor varied inter- and intra-annually from 2.24 in May 2000 to 0.06 in May 2015. As a result, soil losses varied from 0.35 to 617.66 tons per hectare per year (t/ha/year) in a rainy year, and from 0.27 to 1188.92 t/ha/year in a dry year. The combined effects of the slope angle and the vegetation cover were shown to play a major role in soil losses in this area.